A-101 Correspondence between ABAS-II and VABS-II Composite Scales in a Cohort of Adults with Down Syndrome. (17th August 2022) - Ali, Sheliza; Van Pelt, Kathryn; Koehl, Lisa M; Caban-Holt, A M; Anderson-Mooney, A J; Dennis, Brandon; Head, Elizabeth; Harp, Jordan; Glueck, Amanda; Powell, David; Schmitt, Frederick
Abstract: Objective: Informant ratings of adaptive functioning are a valuable source of information that can support diagnosis and treatment planning and monitor change. The Adaptive Behavior Assessment System (ABAS-II) and Vineland Adaptive Behavior Scales (VABS-II) are well-known adaptive functioning questionnaires used in clinical practice. This study assessed the correspondence between ABAS-II and VABS-II composite scales in adults with Down Syndrome (DS). Method: Participants were selected from a cohort of 110 adults with DS involved in a longitudinal study examining Alzheimer's risk. Participants were selected if they had informant ratings on both the ABAS-II and VABS-II at the same measurement wave (n = 85; M = 41.9 years-old, SD = 10.8; 55.3% female; 96.5% White). Due to non-normality, non-parametric correlations examined convergent validity of the ABAS-II and VABS-II standard scores. Results: The composite scores of similar constructs from each measure correlated significantly (ps < 0.001) with large effect sizes: ABAS-II Conceptual with VABS-II Communication (rho = 0.53), ABAS-II Social with VABS-II Socialization (rho = 0.83), ABAS-II Practical with VABS-II Daily Living Skills (rho = 0.84), and ABAS-II Global Adaptive Composite (GAC) with VABS-II Adaptive Behavior Composite (ABC) (rho = 0.88). There was 85.2% correspondence between ABAS-II and VABS-II ratings of low adaptive functioning (SS < 70 on the GAC or ABC, respectively), with just 14.8% of participants (n = 12) categorized as low on VABS-II but not ABAS-II. Conclusion(s): The ABAS-II and VABS-II composites were strongly correlated, capturing similar adaptive domains. However, there was a greater chance of being rated as low functioning on the VABS-II compared to the ABAS-II, which may have diagnostic implications for clinical and research work in DS.